KEBIJAKAN PEMBERIAN ASI EKSKLUSIF BAGI PEKERJA PEREMPUAN DI INDONESIA - Herning Hambarrukmi; Triana Sofiani (MUWAZAH : jurnal kajian gender, 2016)
This paper explores abaout the policy of exclusive ASI (breastfeeding) for women workers in Indonesia. The argument developed during this time are, breastfeeding is the right of every mother, not least women workers, as well as child rights guaranteed by the constitution. However, such rights are not regulated in policies on manpower and civil service. The legal fact, caused by the same values and interests between the state and men based on patriarkhism, so influential in perpetuating gender inequality, including in policies on manpower and civil service